2005
DOI: 10.1038/ja.2005.44
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Structure Assigned to the Antibiotic BU-4664L from Micromonopora

Abstract: The structure assigned to the antitumor antibiotic BU-4664L from Micromonospora sp. was revised to 5,10-dihydro-4,6,8-trihydroxy-10-(3,7,11-trimethyltrans-2,trans-6,10-dodecatrienyl)-11H-dibenzo[b,e][1,4]-diazepin-11-one based on the NMR analysis. Keywords BU-4664L, antitumor, MicromonosporaIn the screening of antitumor compounds from rare actinomycetes, Micromonospora sp. TP-A0860 was found to produce BU-4664L [1] and rakicidins [2]. BU-4664L was originally isolated from Micromonospora sp. M990-6 as a lipoxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…046Eco-11 (Figure S2E). 39 The dibenzodiazepinone core of diazepinomicin is very rare among natural products and to date has only been reported to be produced by Micromonospora strains 15 ,. 16 , 39 Recently discovered BGCs in Streptomyces griseoflavus Tü4000 and in Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…046Eco-11 (Figure S2E). 39 The dibenzodiazepinone core of diazepinomicin is very rare among natural products and to date has only been reported to be produced by Micromonospora strains 15 ,. 16 , 39 Recently discovered BGCs in Streptomyces griseoflavus Tü4000 and in Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation broth was extracted for preliminary characterization of secondary metabolites. We found that only isolate AL7-5 which was identified as M. chalcea could produce rakicidin (McBrien et al, 1995) (Figure 3a) when cultivated on A3M, A11M and A16 and produced compound BU4664L (Figure 3b) only on A16 (Igarashi et al, 2005). 1(2)…”
Section: Screening Of Antimicrobial Activities and Preliminary Characmentioning
confidence: 91%
“…Diazepinomicin has been independently isolated from different Micromonospora strains from different geographic locations of this world by Bristol-Myers Squibb [10,11], Thallion Pharmaceuticals (formerly Ecopia BioSciences) [12], Wyeth [13] and recently by Abdelmohsen et al [14]. So far this compound has never been described outside of the genus Micromonospora .…”
Section: Introductionmentioning
confidence: 99%